Morfologia macroscópica e topografia anatômica do intestino grosso da paca (Cuniculus paca Linnaeus, 1766) - Buerger, Camila Paes; Fernandes Machado, Marcia Rita; Buerger, Karina Paes (Universidade Federal de Santa Catarina (UFSC), 2012)
Exploring the potential of using the paca as livestock involves understanding the morphophysiology of its digestive tract so its nutrition can be properly managed. The morphological and anatomical aspects of the large intestine of this species were investigated by inspecting material that was fresh and fixed in an aqueous solution of 10% formaldehyde. The material was provided by the Setor de Animais Selvagens do Departamento de Zootecnia da Faculdade de Ciencias Agrarias e Veterinarias de Jaboticabal - UNESP (FCAV - UNESP). The large intestine of the paca is formed by cecum, colon and rectum, and is located in the abdominal and pelvic cavity near the third or fourth lumbar vertebrae. It was found, in the 10 samples analyzed, that there was no change in the pattern of this arrangement and that this pattern resembles that of mammals in general.
Gross morphology and anatomy of the large intestine of the paca (Cuniculus paca Linnaeus, 1766).